Ácidos grasos en cepas de microalgas del Banco de Germoplasma de Organismos Acuáticos del Instituto del Mar del Perú (IMARPE) - Hernández Acevedo, Hanna Elizabeth (2019)
In This work, we determinate the fatty acids composition and their nutritional value in 54 microalgal strains, collected from Peru and stored in Banco de Germoplasma de Organismos Acuáticos (IMARPE). The cultures were grown to 50 mL and analyzed by direct transesterification and gas chromatography. In the Chlorophyta group, the microalgaes that present the highest relative percentage of fatty acids were Chlamydomonas reinhardtii (16:0; 41.2%), Scenedesmus obtusus (18:1n-7; 33.6%), Acutodesmus dimorphus (18:1n-9; 37.1%), Desmodesmus armatus (18:3n-3; 32.2%) and Tetraselmis contracta (16:4n-3; 16.5%). Moreover in the Bacillariophyta group, the most abundant fatty acids were 16:1n-7 in Chaetoceros didymus (20.2%), 18:4n-3 in Navicula sp. (28.3%) and EPA in Asterionellopsis sp. (31.5%). By the other hand, in the Dinophyta group, all strains exceed the 20% of DHA, in particular Akashiwo sanguinea, it was strain to have the highest percentage of this fatty acid (29.9%) in addition to 16: 0 (24.8%) and EPA (16%). We discussed uses of these strains is according to their fatty acids content.